The Coexistence of Two Genetic Astrocytopathies—Megalencephalic Leukoencephalopathy and Vanishing White Matter Disease—in an Indian Child - Das, Suman; Ray, Biman Kanti; Chakraborty, Uddalak; Tippabathani, Jayakrishna; Santra, Arindam (Neuropediatrics, 2023)
A 9-month-old male child, born of second-degree consanguinity, presented with a progressively enlarging head since early infancy. The child had normal early development, but further acquisition of milestones after 6 months was delayed. He had afebrile seizures at 9 months, followed by the appearance of appendicular spasticity. First magnetic resonance imaging (MRI) showed nonenhancing, diffuse, bilaterally symmetrical T1/fluid-attenuated inversion recovery (FLAIR) hypointensity and T2 hyperintensity of the cerebral white matter and anterior temporal cysts. Subsequently, the periventricular and deep white matter developed microcystic changes with a pattern of radial stripes. Next-generation sequencing revealed homozygous autosomal recessive variations in the MLC1 gene [c.188T > G, (p.Leu63Arg)] on exon 3 and also in the EIF2B3 gene [c.674G > A, (p.Arg225Gln)] on exon 7, the parents being heterozygous carriers for both variations. This article highlights the rare occurrence of two leukodystrophies of diverse pathogenesis in a child from a nonpredisposed community.
Keywords: leukodystrophies; MLC1; EIF2B; coexistence; MRI